IMPROVING STUDENTS’ MASTERY OF ENGLISH SYNONYMS AND ANTONYMS USING BINGO AND DOMINO GAMES (A Classroom Action Research on the Eighth Grade Students of SMP Negeri 3 Maos in the Academic Year 2013/2014) (ELT Forum: Journal of English Language Teaching, 2015)
This final project is concerned with the use of bingo and domino games in improving students’ mastery of synonyms and antonyms. The objective of this research is to investigate to what extent bingo and domino games give their influence in teaching synonyms and antonyms to the junior high school students. This study used action research design. There were two cycles of action in this study. This research was started with an initial pre-test and ended with a final post-test. In each cycle there were pre-test, treatment, and post-test. Tests were used to collect the quantitative data. Meanwhile, observation checklist and questionnaire were used to gather the qualitative data. The students of class VIIIA of SMP Negeri 3 Maos were chosen as the subjects of this study. The study showed that the games could give a great help to the students in improving their mastery of synonyms and antonyms. By comparing the mean score of initial pre-test and final post-test, a significant improvement could be seen. The students’ mean score of the final post-test (86.95) was higher than that of the initial pre-test (33.09). This improvement was also supported by the results of observation checklists and questionnaire. Based on the observation checklists, the students’ attitude improved. The students’ participation in Cycle 2 was better than that of Cycle 1. Moreover, the result of questionnaire showed that the students gave positive perception towards the use of bingo domino games. By referring to the results, it can be concluded that bingo domino games gave good contribution to the improvement of the students’ ability in mastering English synonym and antonym. Therefore, the use of those games as an alternative way to teach synonyms and antonyms is recommended. Through this technique, teachers are expected to be able to increase students’ interest and motivation in learning synonym and antonym.